Modernisasi Pendidikan Islam Ahmad Dahlan: Perspektif Kesadaran (Konsientisasi) Kritis Paulo Freire - Muhammad Kamaludin; Nafik Muthohirin (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
Ahmad Dahlan was a figure who believed in modern thoughts. He raised awareness of the religious community to dare to think openly to new views, thoughts, and cultures through the modernization of Islamic education and da'wah. Ahmad Dahlan also encouraged religious communities to got out of the trap of poverty and ignorance, as well as the snares of imperialism that occurred in the early 20th century in Indonesia. His reform thinking in the field of religious education was the most prominent in his efforts to integrate Islamic sciences with modern knowledge and culture. This article describes Ahmad Dahlan's thoughts on Islamic education with the educational concept of Paulo Freire called "conscientization" critical awareness. Freire said that the main purpose of education was to liberate society from oppressive colonialism and structural poverty. This article is a research paper with a literature review approach that focuses on the discussion of the modernization concept of Ahmad Dahlan's Islamic education in the perspective of Freire's critical awareness. This manuscript concludes that through the modernization of Islamic education, Ahmad Dahlan has raised critical awareness of the religious community to got out of the shackles of poverty and ignorance, as well as the prison of imperialism.